ANALISA KEBUTUHAN AIRBAGS UNTUK DOCKING UNDOCKING KAPAL TONGKANG VIRGO SEJATI 177 DI PT. YASA WAHANA TIRTA SAMUDERA - Adi Kurniawan Yusim; Ilyasa Fastabiq Ahsan; Bambang Sri Waluyo (Riset Sains dan Teknologi Kelautan, 2021)
PT Yasa Wahana Tirta Samudera (PT YWTS) is a subsidiary of Samudra Indonesia as one of the shipyards in Indonesia, has docking facilities such as Grafing dock (8000 DWT capacity),sliding with 3 docking rails, and airbags technology for and launching barges. Insufficient or excessive air pressure, inappropriate number of airbags and arrangement of airbags that are too close or too far away will have an impact on the ship launching process which may be disrupted and detrimental to the shipyard or owner.This study aims to determine the number of airbags and the distance between airbags during the process of launching the Virgo Sejati 177 with a length of 300 feet.The methods used in this study are From the calculation results of the number of airbags needed in the process of launching the barge, 18 cc airbags were needed. From the calculation results of the number of airbags needed in the process of launching the barge, 18 cc airbags were needed.barges with a cross over type of arrangement is 6.652 - 10.75757 meters.